2007
DOI: 10.1016/j.ijgo.2007.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Dysmenorrhea among Japanese women

Abstract: Dysmenorrhea is common in Japanese women. In our study, about half used self-medication, while some preferred complementary/alternative medicine. Dysmenorrhea is significantly associated with younger age and employment status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 25 publications
8
57
3
Order By: Relevance
“…Other studies reported that adopting weight management programs also caused an increase in menstrual pain (Montero et al, 1996). However, in contrary our study did not find an association between BMI and SFT to the occurrence of dysmenorrhea, studies reported by Ohde et al (2008) supported our findings (Ohde et al, 2008).…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…Other studies reported that adopting weight management programs also caused an increase in menstrual pain (Montero et al, 1996). However, in contrary our study did not find an association between BMI and SFT to the occurrence of dysmenorrhea, studies reported by Ohde et al (2008) supported our findings (Ohde et al, 2008).…”
Section: Resultscontrasting
confidence: 71%
“…Although the effect seen between family size and dysmenorrhea was mild, it was surprising that females from small families were more inflicted than those from large families; the reason for such an observation is difficult to explain. Studies from different regions covering a large number of adolescent population reported socioeconomic status and literacy to have a positive correlation with dysmenorrheal (Klein and Litt, 1988;Patel et al, 2006), contrary to this, Ohde et al (2008) reported no association to income or education with dysmenorrheal.…”
Section: Discussionmentioning
confidence: 66%
“…However, it should be taken into consideration that the age of the university students ranged from 18 to 23 years, and this tight range might explain why the impact of age was not detected in the current study. Other reports concluded that dysmenorrhea peaks in late adolescence, then the incidence falls with increasing age [11,24,25,27]. Also, early menarche was not associated with occurrence of dysmenorrhea which consisted with previous studies [11,28], but did not agree with others [15,16].…”
Section: Socio-demographic and Gynaecological Data Dysmenorrhea N = 1mentioning
confidence: 62%
“…Worldwide, the prevalence of dysmenorrhea varied widely according to the age of the study group, the length of recall/follow-up, and definition of pain whether any pain or pain interrupting with daily activities. In Japan, a prevalence of only 15% was detected in a one-month prospective study over 823 women (18-51 years) [24], while in a study on Chinese women (20-34 years), the 12 months follow-up ported severe pain (8)(9)(10). Forty nine percent reported moderate score of pain (4-7) and the rest of (23%) students had mild pain.…”
Section: Resultsmentioning
confidence: 95%
“…A total of 14 individual studies [3,4,11,[64][65][66][67][68][69][70][71][72][73][74] and two systematic reviews [10,45] presented data on the prevalence and/or incidence rates of dysmenorrhea.…”
Section: Prevalence And/or Incidencementioning
confidence: 99%